Multiple abnormalities in a foetus: a possibility of multifactorial inheritance disorder - D N Sinha (Wolters Kluwer Medknow Publications, 2016)
A female foetus of 3.23 kg was delivered by a primigravida of 23 years, after scanning by ultrasound, depicting findings of oligohydramnios and congenital abnormalities. The foetus showed bilateral Polydactyly (six digits) in both upper and lower limbs, polycystic enlarged bilateral kidneys, anencephaly, hypoplastic lung, small heart, deformed liver etc. The deformed foetus appeared to be the product of multifactorial inheritance disorders in sequential manner where survival of the foetus could not be possible beyond a period.